2020
DOI: 10.1186/s12885-020-07508-7
|View full text |Cite
|
Sign up to set email alerts
|

The association between immune-related adverse events and survival outcomes in Asian patients with advanced melanoma receiving anti-PD-1 antibodies

Abstract: Background The association between immune-related adverse events (irAEs) and survival outcomes in patients with advanced melanoma receiving therapy with immune checkpoint inhibitors (ICIs) has not been well established, particularly in Asian melanoma. Methods We retrospectively reviewed 49 melanoma patients undergoing therapy with ICIs (anti-PD-1 monotherapy), and analyzed the correlation between irAEs and clinical outcomes including progression-free survival (PFS) and overall survival (OS). Results: Overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…The reason is related to the initial time of irAEs. Studies have shown that most irAEs appear within 3 months after the beginning of treatment, while serious adverse reactions such as immune associated pneumonia appear within two months (27). Combined with our clinical data, some patients terminate treatment early due to severe adverse reactions such as immune-related myocardial injury and immunerelated pneumonia.…”
Section: Discussionsupporting
confidence: 58%
“…The reason is related to the initial time of irAEs. Studies have shown that most irAEs appear within 3 months after the beginning of treatment, while serious adverse reactions such as immune associated pneumonia appear within two months (27). Combined with our clinical data, some patients terminate treatment early due to severe adverse reactions such as immune-related myocardial injury and immunerelated pneumonia.…”
Section: Discussionsupporting
confidence: 58%
“…Because of the immortal time bias of irAEs and the intersection points in the overall analysis, we used landmark analysis, in which the irAEs group showed a survival advantage after PFS for 120 days. This finding is related to the initial onset of irAEs: most irAEs reportedly appear within 3 months after the initiation of treatment, while serious adverse reactions such as immune-associated pneumonia appear within 2 months [48]. Our clinical data indicated that some patients discontinued treatment early because of severe adverse reactions such as immune-related myocardial injury and immunerelated pneumonitis.…”
Section: Discussionmentioning
confidence: 58%
“…The relationship between skin irAEs and treatment efficacy has also been previously described, mostly in melanoma and NSCLC [ 41 , 45 ]. A meta-analysis of ICI therapy in melanoma found that vitiligo was significantly associated with both longer PFS and OS [ 46 ].…”
Section: Discussionmentioning
confidence: 98%
“…The positive relationship between AEs of the endocrine spectrum and treatment response has been described in a few studies, both analyzed all together or individually as thyroid dysfunction. As above-mentioned, most studies have described a cohort of patients with melanoma [ 41 ] or NSCLC [ 42 ]. Less is known about endocrine irAEs as a prognostic factor in RCC [ 28 ].…”
Section: Discussionmentioning
confidence: 99%